Numerical Simulation Study on Influence of Riverbed Changes on Saltwater Intrusion in Northwest River Delta - JIN Gaoyang; ZHU Sanhua; CAO Yihao (Renmin Zhujiang, 2024)
To study the changes in the riverbed of the Northwest River Delta and their relationship with saltwater intrusion,this paper builds a one-dimensional unsteady flow chlorine concentration mathematical model based on the collection and organization of previous research results,hydrological,meteorological,and river terrain data.The hydrodynamic and chlorine concentration verification results meet the relevant regulatory requirements and can be applied to calculate and analyze the impact of riverbed changes on saltwater intrusion.The research results are as follows.① From 1999 to 2016, the riverbed of the Northwest River Delta network was in an uneven downward cutting state,and the volume of the river continued to increase,resulting in a decrease in the resistance of the estuary to rising and falling tides.The upward tracing of high saltwater masses along the estuary was simpler,and the upward tracing of salt tides became increasingly severe.② The rising tide at each Koumen station increases,and the probability of removing freshwater from the saltwater boundary decreases.Under different inflow conditions in Sixianjiao,the average upward movement of the saltwater boundary at Modaomen Waterway is 3 735 m,and the average downward movement of the freshwater from Pinggang Pumping Station is 5.33%.The average upward movement of the saltwater boundary at Shawan Waterway is 2 369 m,and the average downward movement of the freshwater from Shawan No.1 Water Plant is 5.14%.These seriously affect the ecosystem and normal water intake demand in the estuarine area.The research results can provide basic support for the research and engineering design of water supply safety measures in the Northwest River Delta and estuarine areas.